The Vortex That Unites Us : Versions of Totality in Russian Literature - Emery, Jacob, 1977- (Book collections on Project MUSE., 2023)
"This book is about the persistent ambition in Russian literature to gather the whole world into the totality of an artwork. The teeming and paradoxical diversity of totalizing figures in the Russian canon, often in alliance with ideologies like the totalitarian state or enlightenment reason, strive for the frontiers of space and time in order to guarantee the coherence of the globe and the continuity of history"--